Büro der Sozialistischen Jugend Internationale: Willi Münzenberg, Julius Mimiola, Ernst Christiansen, Jakob Herzog, Eugen Olaussen, J. W. Schweide
politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Jugendbewegung